PEMBUATAN POT BUNGA DENGAN BAHAN DASAR KAIN BEKAS SEBAGAI MEDIA TANAM KEPADA MASYARAKAT SEI ROTAN - Juli Atika; Hasra Fazri Gusrianda (Jurnal Riset Rumpun Seni, Desain dan Media, 2022)
Garbage is the rest of the goods that are not used in human daily life. In this day and age, waste is a scourge of endless problems in everyday life, most people do not know how to recycle the waste, one of which is the people of Sei Rotan Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. Sei Rotan Village has fertile soil so that the people there, especially mothers, take advantage of the fertile land to channel their hobbies by planting various types of flowers and will place them in the yard of the house, but the Sei Rattan Village women share their hobby of planting flowers with buy the pot even though with the garbage it can produce a beautiful pot. With that we held an activity of making flower pots with used cloth as a planting medium which aims to reduce waste and create creative things such as flower pots from used cloth as a planting medium.The activity of making flower pots from used materials as planting media uses stages as a process to create the flower pot work. In this activity we target the community, especially women in Sei Rotan Village. The waste by creating good works is more than just a pot product such as bags, chairs, etc., and also the people of Sei Rotan Village increase their turnover by selling pots with recycled materials and reducing spending on buying flower pots.